The legend of Arthur in British and American literature - Goodman, Jennifer R. (Jennifer Robin), 1953- (Boston : Twayne Publishers, 1988)
A chronological overview of Arthurian literature.
Includes index.
Bibliography: p. 138-144.
Choice.
Young Adult.
Young Adult
Keywords: American literature -- History and criticism; Arthurian romances -- Adaptations -- History and criticism; Arthurian romances -- History and criticism; English literature -- History and criticism; American literature -- History and criticism; Arthurian romances -- History and criticism; English literature -- History and criticism